2005
DOI: 10.1007/s11095-005-6335-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Tissue Plasminogen Activator Formulated for Pulmonary Delivery

Abstract: Purpose-This study was conducted to assess the feasibility of a pulmonary formulation of tissue plasminogen activator (tPA) for nebulization into the airway by measuring protein stability, biologic activity, particle size, and estimating human lung distribution.Methods-Formulations were derived by varying the surfactant and protein concentrations. Protein stability and recovery of each nebulized tPA formulation were assessed by ultraviolet spectroscopy. Formulations that met protein stability feasibility crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…In this study we showed that tPA, in amounts derived from experimental models, was effective in reducing cast mass ex vivo [10, 15, 25]. This is a reasonable approach for these initial experiments and while this is an encouraging result, much has yet to be done to optimize the pulmonary delivery of this therapeutic protein which appears to have a prolonged elimination in the lungs compared with that of the systemic circulation [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we showed that tPA, in amounts derived from experimental models, was effective in reducing cast mass ex vivo [10, 15, 25]. This is a reasonable approach for these initial experiments and while this is an encouraging result, much has yet to be done to optimize the pulmonary delivery of this therapeutic protein which appears to have a prolonged elimination in the lungs compared with that of the systemic circulation [15].…”
Section: Discussionmentioning
confidence: 99%
“…We report that our PB patients typically produce fibrin, cellular (lymphocytes) casts that are responsive to amounts of tPA that are consistent with those that may be safely delivered to the lungs [10, 15, 25]. …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have previously demonstrated the feasibility of pf-tPA as evidenced by the retention of protein stability and activity following nebulization [13]. In addition, we have proved the concept of the delivery of active protein in a human lung replica by showing that the nebulized particle size distribution would permit diffuse airway distribution.…”
Section: Introductionmentioning
confidence: 91%
“…Lin et al (19) studied how the size of the mouth pieces affected particle deposition. Ali et al (20) and Dunn et al (21) tested metered dose inhalers, dry powder inhalers, and nebulizers for specific medicines with mouth-throat replicas.…”
Section: Introductionmentioning
confidence: 99%